Analysis of The Implementation of Creative Dance in Early Childhood Education - Wulandari, Hayani; Masunah, Juju; Narawati, Tati; Agustin, Mubiar (Universitas Negeri Semarang, 2020)
The purpouse of study to describe the teaching materials and application of creative dance in develop kinesthetic, musical, interpersonal and intrapersonal intelligence. Teaching materials are references that are made and used by teachers to carry out learning activities in the form of daily activity plan, covering learning objectives, content of material to be delivered, time allocation, media to be used until assessment. Teaching materials planning determines the achievement of the objectives of learning activities. This states that planning really needs to be done as well as possible and there is a need for a match between the teaching materials that have been planned and the learning implementation process. This research is a qualitative research with a case study approach conducted in one of the teachers a kindergarten in Purwakarta who was selected by purposive sampling technique. The data were collected by means of observation, interview, documentation and triangulation techniques. The result of the research states that there is a correspondence between the daily activity plan that has been made with the learning implementation process carried out by the teacher. It is hoped that it can continue to be maintained and developed again in the preparation of daily activity plans, so that it can be used by other teachers.